Analysis of the comparisons of farmers benefit that used Rice Thresher Machine and without used Rice Thresher Machine at Pulokerto Subdistrict Gandus District Palembang City - Kurniawan, Rahmat; Wahyudati, Diah (Universitas Muhammadiyah Palembang, 2015)
Analysis of the comparisons of farmers benefit that used Rice Thresher Machine and without used Rice Thresher Machine at Pulokerto Subdistrict Gandus District Palembang City. This research has purpose to analysis the factors of what the influence of the farmers that used Rice Thresher Machine and without used Rice Thresher Machine. And to analysis the differences of the benefit that given by the farmers whoused Rice Thresher Machine and without used Rice Thresher Machine. The method of the research that used in this research was the survey method. The collected sample method used was Disproportionate Stratified Random Sampling with the 60 samples from the farmers, that divided by two groups. Group I was the farmers that used Rice Thresher Machine has 30 farmers. Group II was the farmers without used Rice Thresher Machine has 30 farmers. The method of the collected the data that used in this research was direct interview with the sampling. The data that given from the field should be classes then producted in tabulation. To answer the first problem by mathematics and explained by descriptive with the similar logit regression equation model. Next to analysis and compare the farmer’s payment in group I and group II used the analysis parametric t-test using the SPSS computer application for Windows 16,00.